Wine leads us by our heart not our head: emotions and the wine consumer. (June 2019) - Niimi, Jun; Danner, Lukas; Bastian, Susan EP
Graphical abstract: Highlights: Review of recent publications on wine emotions research. Intrinsic and extrinsic wine factors impact emotions. Wines with similar liking scores may have different emotional profiles. No standardised wine emotions list or understanding of cultural nuances. Individual variation and temporal dimension of wine emotions are not understood. Abstract : The fundamental purpose of wine consumption is for enjoyment. There are deep emotional connections between consumers and wine, and it is usually imbibed in social settings. Consumers' emotions evoked by wine, as well as from external factors during wine consumption, have valuable implications for consumer science and industry. Current perspectives on emotions and wine research are examined with a focus on the role of wine intrinsic and extrinsic factors on consumers' wine-evoked emotions. Future directions of where wine emotions research may head will be explored.